2018
DOI: 10.3390/molecules23092099
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of 5-(3,4-Dihydroxyphenyl)-3-hydroxy-1-(2-hydroxyphenyl)penta-2,4-dien-1-one in Experimental Animal Models of Nociception

Abstract: Curcuminoids derived from turmeric rhizome have been reported to exhibit antinociceptive, antioxidant and anti-inflammatory activities. We evaluated the peripheral and central antinociceptive activities of 5-(3,4-dihydroxyphenyl)-3-hydroxy-1-(2-hydroxyphenyl)penta-2,4-dien-1-one (DHHPD), a novel synthetic curcuminoid analogue at 0.1, 0.3, 1 and 3 mg/kg (intraperitoneal), through chemical and thermal models of nociception. The effects of DHHPD on the vanilloid and glutamatergic systems were evaluated through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…No mortalities were recorded over the 7-day test period and the vital organs were normal upon post mortem examination. The results of the acute toxicity study for DHHPD corroborates the findings reported by Kamarudin et al [15].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…No mortalities were recorded over the 7-day test period and the vital organs were normal upon post mortem examination. The results of the acute toxicity study for DHHPD corroborates the findings reported by Kamarudin et al [15].…”
Section: Resultssupporting
confidence: 90%
“…), which was used as the reference drug, only caused significant inhibition from 2 h onwards. In addition, DHHPD has been shown to reduce the frequency of abdominal constrictions in the 0.6% acetic acid test and the latency of paw licking in the 2.5% formalin test in mice, suggesting its peripheral mechanism in inhibiting the release of inflammatory mediators responsible for pain [15]. These results indicate that DHHPD may act on the COX enzymes or prostaglandin synthesis from arachidonic acid through a mechanism similar to that of aspirin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The E. globulus and S. didymobotrya leaf extracts showed significant analgesic effects by reducing pain in mice in the early and late phases. The demonstrated effects were both peripheral and central (23). The central analgesic activity could have been due to inhibition of the nociceptive effects of noradrenaline, bradykinin, prostaglandins, adrenaline, adenosine, serotonin, and acetylcholine.…”
Section: Discussionmentioning
confidence: 98%
“…Each animal received an intraperitoneal injection of 0.85% ( v / v ) acetic acid in saline and was then placed in a polyethylene box to record the latency period (time until the first writhing) and the number of writhes in the interval corresponding to 5–15 min after the injection of acetic acid (CEEA process N o . 23076.015163/2017-65) [59].…”
Section: Methodsmentioning
confidence: 99%